Sosialisasi Motivasi Kewirausahaan dan Peluang Bisnis Online pada Industri Makanan Halal Kota Pangkalpinang - Eka Fitriyanti (Indonesian Journal of Dedication and Educations, 2022)
Counseling and motivation to foster entrepreneurialinterest and online business opportunities in improving the halalfood industry in the city of Pangkalpinang are urgently needed,one of these solutions is to increase the entrepreneurial spirit ofevery halal food MSME actor in the area. The purpose of thiscommunity service is to socialize and foster entrepreneurialmotivation and see online business opportunities to improve thehalal food industry in the city of Pangkalpinang. The service iscarried out at the production site of each halal food MSME. Themethod of community service activities begins with thepreparation stage, this activity first seeks participant data atLPPOM MUI, Bangka Belitung Islands Province. Furthermore,the implementation stage of material presentation activities iscarried out by presenters delivering socialization material andentrepreneurial motivation, and online business opportunities.The results of this activity indicate that the MSME halal foodbusiness actors in Pangkalpinang City, after participating in thesocialization and entrepreneurial motivation of the participants'knowledge, in this case, the majority of halal food MSME actorswere in the category of not understanding the concept ofentrepreneurship and less motivated because they did notunderstand the potential. But after the PKM activities werecarried out and the presentation of the material was delivered, itwas found that the participants' knowledge aboutentrepreneurship and entrepreneurial self-potential and the useof online media in doing business had increased.